Effects of palm oil on lipid peroxidation, reduced glutathione, glutathione peroxidase, and vitamin a levels in the corpus uteri, cornu uteri and corpus luteum of young and adult female sheep - Yildiz, S.; Naziroglu, M.; Kaya, I.; Aydilek, N.; Yuce, A. (Blackwell Verlag GmbH Berlin, 2002)
The aim of the current study was to determine whether a rumen protected palm oil based diet affect malondialdehyde (MDA), glutathione peroxidase (GSH-Px), reduced glutathione (rGSH) and vitamin A levels in the tissues of cornu uteri, corpus uteri and corpus luteum over the barley based isoenergetic and isonitrogenous diet, and whether the response is different between ewes and ewe-lambs. During the breeding season, half of Morkaraman ewes (2-4-year-old, n = 10) and ewe-lambs (7-8-months-old, n = 10) was offered a barley based diet and the other half was offered a protected palm oil based diet for 42 ± 0.7 days. At the end of the experiment all animals were slaughtered and measurements carried out in the tissues collected. In all animals tested, cornu uteri had the highest MDA levels followed by corpus uteri and corpus luteum (P < 0.01) but no differences were between the tissues observed in GSH-Px and rGSH levels (P > 0.05). Vitamin A levels were, however, higher in corpus luteum than in cornu uteri and corpus uteri (P < 0.05). Corpus uteri MDA levels were not different (P > 0.05) but rGSH levels were higher for the palm oil fed groups (P < 0.05). GSH-Px and rGSH levels were higher for ewe-lambs than ewes (P < 0.05). In conclusion, it appears that MDA, rGSH, GSH-Px, and vitamin A work in a different fashion for corpus uteri, cornu uteri and corpus luteum, and for ewes and ewe-lambs. Dietary palm oil did not significantly affect the parameters studied except higher rGSH levels in corpus uteri. Levels of antioxidatively active substances, such as rGSH and GSH-Px were lower in ewes compared with those in ewe-lambs.
Keywords: Animals; Corpus Luteum; Diet; Female; Glutathione; Glutathione Peroxidase; Lipid Peroxidation; Malondialdehyde; Plant Oils; Sheep; Uterus; Vitamin A; glutathione; glutathione peroxidase; malonaldehyde; palm oil; retinol; vegetable oil; animal; article; corpus luteum; diet; drug effect; female; lipid peroxidation; metabolism; sheep; uterus